Secularização e espaço público - Carneiro, Luís (Trabalhos de Antropologia e Etnologia, 2020)
The present paper will aim at tracing a relationship between the multiform concept of secularization and the contemporary configuration of public space, for this purpose we will appeal to the work of several authors converging on the analysis of secularization and the perspectives on the idea and reality of public space which stem from this analysis. The notion of secularization presents itself according to a complex variety of meanings, for the purpose of the present paper it will be envisaged as a concept which signals the persistency and immanence of theological categories in political structures, based on Carl Schmitt’s preliminar definition, according to which all significant concepts of the modern theory of the state are secularized theological concepts. It will be mostly following from this general meaning that certain aspects of the contemporary debate, led by Jürgen Habermas, on the relationship between religion and public space will be clarified.